$\frac{(3*4*(2^16))^2}{(11*(2^13)*(4^11)-(16^9)}$

Question

$\frac{(3*4*(2^16))^2}{(11*(2^13)*(4^11)-(16^9)}$

in progress 0
aikhanh 1 năm 2021-09-04T09:27:44+00:00 2 Answers 10 views 0

Answers ( )

    0
    2021-09-04T09:28:48+00:00

    *Lời giải  :

    `( (2. 4 . 2^{16})^2)/(11 . 2^{13} . 4^{11} – 16^9)`

    `= (2^2 . 2^4 . 2^{32})/(11 . 2^{13} . 2^{22} – 2^{36})`

    `= 2^{38}/(11 . 2^{35} – 2^{36})`

    `= 2^{38}/(2^{35} . (11 – 2) )`

    `= 2^3/(11 – 2)`

    `= 8/9`

     

    0
    2021-09-04T09:29:16+00:00

    $\frac{(3 .4.(2^{1}.6))²}{(11.(2^{1}.3).(4^{1}.1)-(16^{9})}$

    =$\frac{(12.12)²}{11.6.4-4^{18}}$

     =$\frac{12^{4} }{4(66-4^{18})}$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )